(untitled) (Journal of the College of Basic Education, 2022)
Existential theater is considered one of the most prominent currents and doctrines that emerged at the beginning of the twentieth century. Its works reflected the philosophy of (existentialism), especially its modern manifestations in (Jean-Paul Sartre), (Albert Camus), (Simon de Bevoir) and others, that philosophy that glorified (individualism) and the subjective spirit as a kind It is a protest against all the metaphysical and ideological tendencies that cancel the role of man and deprive him of his freedom. It is a theater centered around awareness and rejection.The existential doctrine was not satisfied with philosophical and intellectual expression, but rather invested its philosophy and employed it in theatrical works and attempted to marry philosophical thought and artistic vision.